Struktur sintaksis frasa nama Bahasa Bateq - Fazal Mohamed Mohamed Sultan, (Penerbitan UKM, 2009)
Malaysia has some distinctive speakers who can speak Austroasiatics languages. However, the number of Austroasiatics languages in Malaysia is comprised of only 18 languages (Jabatan Orang Asli, 2009). These languages are very small in numbers; therefore, this has contributed to the criticality of these languages because they may extinct (Benjamin, 1976). One of these languages that is experiencing the process of extinction in Malaysia is Bateq language, which is spoken by Orang Bateq at Perkampungan Pos Pasir Linggi, Kelantan. The total number of Orang Bateq at the moment is only as many as 300 people. However, this study has a very narrow focus, which is the syntactic analysis of Bateq’s noun phrase (NP). The descriptive analysis will elucidate the noun phrase and the word order, which form the noun phrase of Bateq Further, guided with the descriptive analysis, writer will argue the syntax of the NP structure of the Bateq language using the X-bar theory framework (Chomsky, 1986). Resulted from this analysis, the writer will put on view the adjunction structure of Bateq’s NP